Organisational Metamodel for Large-Scale Multi-Agent Systems: First Steps Towards Modelling Organisation Dynamics - OkreŠa Ðuri?, Bogdan (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2017)
The research presented in this paper is a thesis proposal with the main goal of defining an ontology comprising chosen organisational concepts applicable to large-scale multiagent systems (LSMAS), and building a metamodel for modelling selected organisational features in such systems. The method of applying aspects of human organisations to multiagent systems (MAS) comprising autonomous intelligent agents will be enriched through this research with a new perspective of modelling organisation dynamics in LSMAS. Results of this research, in their final version, will be tested using testbed scenarios based on a specific massively multi-player online role-playing game (MMORPG), since MMORPGs are one of the identified application domains of LSMAS. It is important to note that results described in this paper showcase partial results in their early stage of development. Nevertheless, first traces of a modelling tool that is expected to aid in development of LSMAS for numerous application domains, and ease their organisational design, are recognisable in the proposed combination of ontology engineering, metamodelling and code generating methods.